Tourism making places at the Norwegian–Russian border – Narratives amidst geopolitical change - Naukkarinen, Sanni (UiT Norges arktiske universitet, 2023)
This thesis discusses the construction of place through place narratives on the Norwegian–Russian border in the town of Kirkenes, Northern Norway. Based on ethnographic fieldwork from April to July 2022, the study explores how tourism to the Russian border constructs three places: Russia, Kirkenes in relation to Russia, and the Norwegian–Russian border. Border tourism is analysed in light of geopolitical turmoil due to the Russian aggression in Ukraine, and its impact on local identity and cross-border relations. Inspired by Doreen Massey’s (1994) theory of place, this thesis analyses how the local tourism industry negotiates places between insiders (locals) and outsiders (tourists), presenting local narratives, tourists’ narratives and narratives created on the border tours. Following Margaret Rodman’s (1992) notion of multilocality, place is seen as consisting of multiple realities as it is experienced differently. It is argued that narratives of Russia affect how people perceive place on the Norwegian–Russian border. Furthermore, it is contended that the locals and the tourists perceive the place in distinct ways, as the local and tourists’ narratives differ – and even oppose one another. The collective memory of Russians as friendly neighbours has contributed to positive narratives of Russia in Kirkenes, while the tourists arrive at the border with Western narratives of Russia as the “antagonist Other”. The tourism industry distributes both these opposing narratives. The geopolitical situation is affecting the narratives and it is argued that the Russian border is now perceived by outsiders as a place of reactivated tension, both attracting and repelling visitors, while for the locals the border remains a rather neutral reality. At present, however, Kirkenes’ local narratives of Russia and of the relationship with Russians are becoming contested.